New SMEs Products Development and Improvement of Competitiveness Compliance Towards Food Standards in Sijeruk Village Banjarmangu Districts Banjarnegara Regency - Astohar Astohar; Andi Kartika; Sari Rahmadhani; Muhamad Saufi Che Rusuli; Rahul Bhandari; Nico Irawan; Chanwut Thongkamkaew; Mulyani Mulyani; Paskah A Sinaga (Universitas Muhammadiyah Manado, 2021)
Micro, Small, and Medium Enterprises (MSMEs) in Sijeruk village, Banjarmangu district, Banjarnegara regency have shown significant development. However, there remain several challenges faced by UMKM entrepreneurs, including limited marketing outreach, financial reports intertwined with household finances, and inadequate innovation in product development and packaging. This community service initiative aims to address these issues effectively.